Gender Norms and Network Structure: A Model of the Intrahousehold Division of Labor. - Hager, Theresa; Mellacher, Patrick; Rath, Magdalena (Feminist Economics, 2025)
This study presents a bargaining model with endogenous gender norms. Agents are heterogeneous in their wage rates and preferences but seek to conform to the behavior of their social reference group. In contrast to the previous literature, which assumes a homogeneous social norm, agents are connected through explicitly modeled social networks and thus face heterogeneous gender norms. In this model, social pressure to conform to gender norms exacerbates gender inequalities in the distribution of paid and unpaid labor resulting from a gender pay gap or gender-specific preferences. However, a heterogeneous norm causes agents to act significantly different from – and, on average, more egalitarian than – a homogenous norm. The differences are particularly strong if agents are more likely connected with others who have similar preferences. The findings suggest that technological revolutions such as social media could impact the intrahousehold division of labor by changing the social reference group of individuals. HIGHLIGHTS The study introduces a theoretical model of the intrahousehold division of labor influenced by gender norms. People want to conform to the behavior of others (gender norms). People only observe the behavior of a subset of the population. Network-mediated norms produce more egalitarian outcomes than a global norm. Study emphasizes the importance of considering network structures in gender norm studies.